ISOLATION, CHARACTERIZATION AND PATHOGENIC POTENTIAL OF FUNGI FROM WASHING MACHINES - Omotoso, Opeyemi G.; Ayandele, Abiodun A.; Omotoso, Ifeoluwa O.; Amao, Ayobami J.; Adiamo, Opeyemi D.; Salaudeen, Habibat B.; Gbodi, Oyepeju A.; Ojelade, Blessing T. (FUDMA Journal of Sciences, 2026)
This study aimed to profile the antifungal resistance pattern of fungi isolated from washing machines sampled from hospitals, hotels, student hostels, homes and laundry services shops in Ogbomoso. Isolation procedures for collected samples were carried out using standard microbiological techniques. Fungal isolates were subjected to antifungal drugs to determine their susceptibility pattern. Isolates with multiple resistance ≥ 60 % were selected for molecular characterization. The ability of the selected isolates to produce biofilm was assessed and quantified at 492nm and toxin production was also determined. The potential of the fungi to produce enzymes such as protease, amylase, cellulase, pectinase and collagenase were screened. Questionnaires were given to the staff of hotels and laundry service shops on the treatment of washing machines. A total of 24 fungal isolates belonging to 5 genera of Aspergillus, Trichoderma, Candida, Cladosporium and Alternaria. Aspergillus species were found to be the predominant (70.8%). The highest resistance to anti-fungal drugs employed was from Aspergillus niger with 80% resistant. Aspergillus niger was the only biofilm producer, belonging to the weak biofilm former. Two isolates out of the selected four fungi were able to produce aflatoxins while they all have the potential to produce more than five enzymes. Both the hotels and laundry services are frequently (82%) treated and their source of water is treated once in a month as reported by 63% of the respondents. Washing machines sampled in this study were reservoirs for multi-anti-fugal drug- resistant isolates, and this could pose serious threat to public health.